1999
DOI: 10.1063/1.479130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of basis set and electron correlation on the calculated interaction energies of hydrogen bonding complexes: MP2/cc-pV5Z calculations of H2O–MeOH, H2O–Me2O, H2O–H2CO, MeOH–MeOH, and HCOOH–HCOOH complexes

Abstract: The MP2 intermolecular interaction energies of the title complexes were calculated with the Dunning’s correlation consistent basis sets (cc-pVXZ, X=D, T, Q, and 5) and the interaction energies at the basis set limit were estimated. The second-order Mo/ller–Plesset (MP2) interaction energies greatly depend on the basis sets used, while the Hartree–Fock (HF) energies do not. Small basis sets considerably underestimate the attractive interaction. The coupled cluster single double triple [CCSD(T)] interaction ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
91
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 83 publications
15
91
0
1
Order By: Relevance
“…The performance of MP2 methods for properties involving making or breaking electron pairs is substantially inferior to that of CCSD(T) and also not as good as the best DFT methods, although recent results have come closer to DFT benchmarks (14). However, for most systems, MP2 does extremely well for nonbonded interactions and internal conformational energetics, typically delivering accuracy within Ϸ0.3 kcal͞mol if one extrapolates to the basis set limit (15,16,23). A recent interesting exception has been noted for stacking interactions of the benzene dimer, where CCSD(T) corrections are required to avoid errors in the range of 0.5-1.0 kcal͞mol (17); more investigation will be required to enumerate other outliers of this type.…”
Section: Quantum Chemical Theorymentioning
confidence: 99%
“…The performance of MP2 methods for properties involving making or breaking electron pairs is substantially inferior to that of CCSD(T) and also not as good as the best DFT methods, although recent results have come closer to DFT benchmarks (14). However, for most systems, MP2 does extremely well for nonbonded interactions and internal conformational energetics, typically delivering accuracy within Ϸ0.3 kcal͞mol if one extrapolates to the basis set limit (15,16,23). A recent interesting exception has been noted for stacking interactions of the benzene dimer, where CCSD(T) corrections are required to avoid errors in the range of 0.5-1.0 kcal͞mol (17); more investigation will be required to enumerate other outliers of this type.…”
Section: Quantum Chemical Theorymentioning
confidence: 99%
“…They have been thoroughly studied by a variety of experimental and theoretical methods [2,3,4,5,6,7,8,9,10,11,12,13,14,15] so that the strengths of the common hydrogen bonds in biological systems are accurately known.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous phase interactions may however alterthe energetics of the reaction. A number of complexes are fonned between fonnaldehyde and water due to strong hydrogen bonding (Kumpfand Damewood, 1989;Tsuzuki et al, 1999;Turner et al, 2000;Chandra et al, 2000). Computations carried out by G. Koyanagi (private communication) showed that the transition state and final product enthalpies are reduced if solvation effects are taken into consideration.…”
Section: Pan and Ch 1 Co·0mentioning
confidence: 99%